PENGARUH CAPITAL INTENSITY, PROFITABILITAS DAN LIKUIDITAS TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN PERTAMBANGAN - Nur Rohman; Siti Alliyah (ITB AAS INDONESIA, 2024)
The objective of tax aggressiveness is to minimise the tax liability of a business, whether through lawful or unlawful methods. The study's overarching goal is to identify, for the years 2017–2021, any relationship between mining companies' tax aggression, capital intensity, profitability, and liquidity. In this study, tax aggressiveness is the dependent variable, whereas liquidity, profitability, and capital intensity are the independent variables. It consists of all mining companies that were listed on the BEI between 2017 and 2021. The data collection methodology for this study combined the documentation method with the purposive sampling method to obtain samples that fit the research criteria. The research cohort included 13 different businesses and a grand total of 65 observations. This research made use of SPSS-based multiple linear regression analysis to examine the collected data. Preliminary testing of the SPSS application was conducted using classical assumptions to collect data that demonstrated the best linear unbias estimate (BLUE). A favourable correlation between Capital Intensity and tax aggression seems to exist, according to the results of this study. It is clear that tax aggression is significantly impacted negatively by profitability. Liquidity and tax aggression are positively correlated, however weakly.